Intelligent remote/trigger : a photographer’s buddy (Arduino based) - Rajadorai, Naveend (2018)
High-speed photography is an art, of capturing a desired image at a specific moment. That moment can occur in a fraction of a second. Some examples of such moments are, shattering of glass, popping of balloon etc. To carry out these moments, a projectile is to be shot at the desired object. However, as a catapult was used to shoot the projectile, the accuracy was minimal.